Community forestry adoption based on multipurpose tree species diversity towards to sustainable forest management in ICEF of University of Lampung, Indonesia - CHRISTINE WULANDARI; AFIF BINTORO; RUSITA RUSITA; TRIO SANTOSO; DURYAT DURYAT; HARI KASKOYO; ERWIN ERWIN; PITOJO BUDIONO (Society for Indonesian Biodiversity, 2018)
Wulandari C, Bintoro A, Rusita, Santoso T, Duryat, Kaskoyo H, Erwin, Budiono P. 2018. Community forestry adoption based on multipurpose tree species diversity towards to sustainable forest management in ICEF of University of Lampung, Indonesia. Biodiversitas 19: 1102-1109. Integrated Conservation Education Forest (ICEF) of University of Lampung (Unila) at Wan Abdul Rachman (WAR) Forest Park is a conservation forest which should be free from any kinds of human activities. In fact, more than 75% the area has been managed by community hence there is a need for management strategy through Community Forestry (CF). It is known that there are a lot of Multipurpose Tree Species (MPTS) that can be utilized for the community’s daily life. The research’s objectives are to analyze the ability of the community to adopt CF scheme, to calculate the diversity index of MPTS and level of Skill Knowledge Attitude (SKA) and to determine the correlation variables to sustainable CF. This study used Shannon-Wiener diversity index, analysis of SKA level and regression analysis for adoption level. The results of this study noted that at the research site has diversity index 0.115 and 74.29% of plants are MPTS. Based on the data analysis, 168 respondents [89%] agree to adopt CF scheme and level of their SKA is moderate therefore needs to increase this level towards to forest sustainability. There are three variables of community forestry adoption toward to sustainable forest management at ICEF: number of trees species, the volume of forest products that would be sold, and roles of extension education.